Features of cast iron for railway brake pads - E. A. Sirenko (Литьë и металлургия)
The paper presents the results of comparison of quality indices of brake shoes for railroad rolling stock made of synthetic cast iron smelted in induction furnaces and of composite material which is a vulcanized mixture of rubber and different fillers. Disclosed are the disadvantages of composite brake pads. Defects of the working surface of the railway rolling stock wheels rolling surface caused by the application of composite brake pads made of rubber-asbestos or rubber-asbestos mixture are shown. Parameters of C, Si, Mn, P, S content and carbon equivalent distribution in cast iron used for the production of «M» type brake shoes according to GOST 30249-97 are analysed. It is established that the hardness and fracture strength of pads do not correlate with the content of chemical elements in cast iron and its carbon equivalent. The ranges of C, Si, Mn, P, S distributions in the specified purpose cast iron are much narrower than the allowable limits of these elements specified in GOST 30249–97. Suggestions for improving the standards are given.